The Works of A Ma'rifa as A Phenomenon of Spiritual Counseling in Handling Non-Positivistic Psychic Problems - Hajir Tajiri; Umi Rohmah; Fathin Anjani Hilman (IAIN Ponorogo, 2022)
Life's problems cannot always be solved only with a rational approach. Sometimes there are a number of problems that the client perceives as confusing, unrelieved illness, loss of valuables and spiritual disturbances. This situation encourages them to go to experts of hikmah in the hope of getting help. This is what clients who come to the hikmah experts at the Tasikmalaya Mubarok Foundation do. The purpose of this study is to identify the steps of the wisdom expert in helping clients who experience non-positivistic difficulties in their lives, and to confirm the way of handling by the wisdom expert as a model of spiritual counseling. That what the wisdom expert does, which begins with asking the client to convey his life complaints and is encouraged to reflect on past mistakes, then the client is asked to repent, commit to doing good deeds and want to carry out the practice suggested by the wisdom expert. This stage bears fruit, some problems of non-positivistic life are successfully solved. The perspective of spiritual counseling guidance states that efforts to handle life problems by involving religious beliefs held by wisdom experts in helping non-positivistic clients' life problems are one model of spiritual counseling. Thus the results of this study contribute to the development of spiritual counseling, especially in the Muslim community.